2008
DOI: 10.1007/s00167-008-0626-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imagination of the peroneus longus tendon after anterior cruciate ligament reconstruction

Abstract: Several studies report that tendons can regenerate after harvesting. These studies have been performed especially in patellar and hamstring tendons. At our institution, 10 cm length of full thickness peroneus longus tendon has been harvested to reconstruct torn anterior cruciate ligament since 1997 as a different graft source. The aim of this study was to investigate whether the peroneus longus tendon used the anterior cruciate ligament reconstruction has a regeneration potential or not. Twelve patients, who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
(32 reference statements)
1
25
0
2
Order By: Relevance
“…Similarly, another study reported that PLT could regenerate after harvesting. 14 In 12 patients who had undergone full-thickness PLT harvesting, a varying amount of regeneration was seen on MRI. The mean percentages of regeneration were 59.2%, 49.9%, and 44.5% in the proximal, middle, and distal sections, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, another study reported that PLT could regenerate after harvesting. 14 In 12 patients who had undergone full-thickness PLT harvesting, a varying amount of regeneration was seen on MRI. The mean percentages of regeneration were 59.2%, 49.9%, and 44.5% in the proximal, middle, and distal sections, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,16,39 However, limited studies are available regarding tendon regeneration after PLT harvesting. 14 Moreover, no report of tendon regeneration after AHPLT harvesting is available.…”
mentioning
confidence: 99%
“…Peroneus tendons are an alternative to reconstructing ligaments to prevent morbidity from donor sites in another tendon [5]. Kerimoglu studied 12 patients who underwent ACL reconstruction using peroneus longus tendon grafts with follow-up ranging from 18 to 96 months using MRI and found that there was a regeneration of peroneus longus tendons and there was no disturbance in ankle function and exercise [11].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of ACL reconstruction is to restore knee stability, relieve pain and instability symptoms, and return the patient to daily activities [1]. There are several graft choices used in ACL reconstruction, one of which is the peroneus longus tendon graft [2]. Peroneus longus autograft is an effective and safe graft as an alternative to ACL reconstruction [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation